2020
DOI: 10.21037/atm-20-7652
|View full text |Cite
|
Sign up to set email alerts
|

Hand eczema among healthcare workers in Guangzhou City: a cross-sectional study

Abstract: Background: Healthcare workers are at high risk of developing hand eczema. This study aimed to investigate the association between occupational hygiene and self-reported hand eczema among nurses and doctors in Guangzhou. Methods:A cross-sectional study using a self-administrated questionnaire sent to 740 health care workers in two tertiary hospitals between 1 st April and 1 st July 2019 was conducted.Results: In total, 521 healthcare workers responded (70.4%). The prevalence of self-reported hand eczema was 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Only one study was found eligible with respect to the incidence of HE. Although several studies have been published in the past years with data on the incidence of HE in HCWs, these were not included owing to missing data 44 or the use of symptom‐based diagnosis 34 . The Danish study included in this review reported an incidence of 34 cases per 1000 person years, 31 which is markedly higher than in the general population with an incidence of 7.3 cases per 1000 person years 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Only one study was found eligible with respect to the incidence of HE. Although several studies have been published in the past years with data on the incidence of HE in HCWs, these were not included owing to missing data 44 or the use of symptom‐based diagnosis 34 . The Danish study included in this review reported an incidence of 34 cases per 1000 person years, 31 which is markedly higher than in the general population with an incidence of 7.3 cases per 1000 person years 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated for an assumed prevalence of 19% with an absolute precision of 5% based on previous studies. [4][5][6] A minimum of 250 participants were required to find a statistically significant difference. The questionnaire was distributed to 400 HCWs of which 257 responded, hence the results are analyzed for 257 HCWs.…”
Section: Study Populationmentioning
confidence: 99%
“…Several studies worldwide have reported that occupational skin disease prevalence in HCWs is between 8 and 90%. [4][5][6] The symptoms of HD include itching, swelling, redness, burning, and scaling. Stringent hand hygiene measures result in the loss of surface lipids, leading to an increase in trans-epidermal water loss, and increasing the penetration of allergens and irritants resulting in HD.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Huang et al reported that health workers who used latex gloves more than 10 hours per day mostly experienced hand eczema symptoms due to latex. 5,6 Hand eczema is a recurrent inflammatory skin disease characterized by red skin lesions, papules, vesicles, scales, itching, and pain. Recurrent hand eczema can interfere with daily activities and cause psychological disorders, which commonly occur in health workers.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent hand eczema can interfere with daily activities and cause psychological disorders, which commonly occur in health workers. 4,6 Based on this description, the purpose of this study was to determine the correlation between the frequency of handwashing and the duration of using latex gloves on the incidence of hand eczema. In addition, this study hopefully would provide beneficial information to prevent hand eczema, especially for health workers during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%